Anisotropic energy transfer in a clay–porphyrin layered system with environment-responsiveness. Issue 25 (19th June 2020) - Nishina, Haruka; Hoshino, Shota; Ohtani, Yuta; Ishida, Tamao; Shimada, Tetsuya; Takagi, Shinsuke
Abstract : The adsorption orientation behavior of tetrakis(1-methylpyridinium-3-yl)porphyrin ( m -TMPyP) and p -TMPyP on the clay monolayer prepared by the Langmuir Blodgett (LB) technique was investigated using the absorption and dichroic spectra obtained on a waveguide. Abstract : The adsorption orientation behavior of tetrakis(1-methylpyridinium-3-yl)porphyrin ( m -TMPyP) and tetrakis(1-methylpyridinium-4-yl)porphyrin ( p -TMPyP) on the clay monolayer prepared by the Langmuir Blodgett (LB) technique was investigated using the absorption and dichroic spectra obtained on a waveguide. It was revealed that the orientation of m -TMPyP and p -TMPyP on the clay monolayer, that is parallel and tilted with respect to the clay surface, depends on the surrounding environments such as water and N, N -dimethylformamide (DMF). The anisotropic photochemical energy transfer between m -TMPyP as a donor and p -TMPyP as an acceptor in the layered system was investigated in water and in DMF–water (9/1 (v/v)) by a fluorescence observation. As a result, while energy transfer efficiency ( η ET ) was 60% for the parallel–parallel orientation in water, that was 10% for the tilted–tilted orientation in DMF–water (9/1 (v/v)). The major factor for the change of η ET could be a change of the distance between m -TMPyP and p -TMPyP, and the J value that is a parameter for spectral overlap between energy donor's fluorescence and acceptor's absorption.